Integrated physiological and transcriptomic analyses elucidate the molecular mechanisms of exogenous melatonin-mediated salt tolerance in pomegranate (Punica granatum L.) - Yang, Yuanling; Liu, Huiying; Gai, Haosheng; Liu, Yang; Liu, Mingxuan; Wu, Linnan; Diao, Ming (Frontiers in Plant Science, 2025)
Salt stress is a critical constraint affecting the cultivation of Tunisian soft-seeded pomegranate (Punica granatum L.). To elucidate the molecular mechanisms underlying exogenous melatonin (MT)-mediated enhancement of salt tolerance in pomegranate seedlings, this study integrated physiological phenotyping and transcriptome sequencing to systematically investigate MT’s regulatory effects on antioxidant systems, photosynthetic apparatus function, osmotic adjustment, and core metabolic pathways under salt stress. The results demonstrated that 200 mM NaCl treatment induced reactive oxygen species (ROS) overaccumulation, elevating malondialdehyde (MDA) content and relative electrical conductivity (REC) by 0.43 and 0.46 fold, respectively. Concurrently, salt stress severely impaired photosynthetic performance: PSII maximum photochemical efficiency (FV/FM) decreased by 44.5%, actual photochemical efficiency (YII) and photochemical quenching (qP) were reduced, and non-photochemical quenching (NPQ) increased, indicating serious photoinhibition and energy wastage. In contrast, 400 μM MT treatment effectively mitigated oxidative damage by coordinated activation of superoxide dismutase (SOD,+14.3%), peroxidase (POD,+21.7%), and catalase (CAT,+11.7%) activities, thereby stabilizing membrane integrity. Furthermore, MT significantly alleviated photoinhibition: FV/FM increased by 39%, YII and qP rose, and NPQ decreased compared to salt-stressed plants, reflecting enhanced protection of the PSII reaction center and optimized light energy allocation. Transcriptomic analysis reveals that MT treatment is associated with alterations in the expression of key sucrose metabolism genes, including the upregulation of SUCROSE SYNTHASE (SUS) and UDP-GLUCOSE PYROPHOSPHORYLASE (UGP2), as well as the recovery of GLYCOGEN SYNTHASE (glgA) expression following salt stress inhibition. These changes suggest a potential role for MT in modulating carbon metabolic homeostasis. Additionally, MT application is linked to expression changes in genes within the Mitogen-Activated Protein Kinase (MAPK) signaling pathway. Concurrently, broad expression variations are observed in genes associated with multiple phytohormone signaling pathways. Weighted gene co-expression network analysis (WGCNA) further identifies two core gene modules: the blue module is enriched with antioxidant-related genes (e.g., LOC116212144), while the yellow module is closely associated with genes implicated in membrane stability (e.g., LOC116203737). Integrated physiological and transcriptional evidence indicates that exogenous melatonin may enhance salt tolerance in pomegranate seedlings by activating the antioxidant system, protecting photosynthetic apparatus, regulating carbon metabolism, and influencing multiple signal transduction pathways. This study provides a theoretical foundation for further elucidating the mechanistic basis of MT-mediated salt adaptation in plants.